Epigenetic reprogramming in cloned embryos. - Nam-Hyung Kim
Although nuclear transfer (NT) techniques are used to clone animals, their efficiency is very low. Moreover, NT has resulted in offspring with severe developmental problems, probably due to incomplete nuclear reprogramming. Nuclear reprogramming is characterized by functional modification of the transferred nucleus to allow it to direct normal embryo development with the potential to grow to term. Although the nature of the reprogramming factor(s) in mammals is not clear, various nuclear as well as cytoplasmic components are involved in the processes. In this article we review recent data on factors associated with the nuclear reprogramming of cloned embryos.
Keywords: Clone animals; Cytoplasmic components; Direct normal embryo development; Nuclear reprogramming; Nuclear transfer techniques; Severe developmental problems